2003
DOI: 10.1097/01.ogx.0000090198.17755.85
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Review of 208 Patients With Leiomyosarcoma of the Uterus: Prognostic Indicators, Surgical Management, and Adjuvant Therapy

Abstract: This study was conducted to identify clinical factors that are predictive of treatment choice for pelvic organ prolapse. One hundred forty-six women diagnosed with pelvic organ prolapse were educated about their condition and possible treatments before being offered one of three different treatment choices: expectant management (any choice other than pessary or surgery, including pelvic muscle exercises), pessary, or surgery. Data were recorded for all factors that might be predictors of treatment choice, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
107
0
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(125 citation statements)
references
References 32 publications
5
107
0
13
Order By: Relevance
“…Uterine sarcomas are rare tumors that account for approximately 1% of female genital tract malignancies and 3%-7% of uterine cancers [1]. Although the aggressive nature of most cases is well recognized, their rarity and histopathologic diversity have contributed to the lack of consensus on risk factors for poor outcome and optimal treatment [2]. Until now, the 1988 International Federation of Gynecology and Obstetrics (FIGO) criteria for endometrial carcinoma have been used to assign stages for uterine sarcomas despite the different nature of both tumor categories.…”
mentioning
confidence: 99%
“…Uterine sarcomas are rare tumors that account for approximately 1% of female genital tract malignancies and 3%-7% of uterine cancers [1]. Although the aggressive nature of most cases is well recognized, their rarity and histopathologic diversity have contributed to the lack of consensus on risk factors for poor outcome and optimal treatment [2]. Until now, the 1988 International Federation of Gynecology and Obstetrics (FIGO) criteria for endometrial carcinoma have been used to assign stages for uterine sarcomas despite the different nature of both tumor categories.…”
mentioning
confidence: 99%
“…Stage appears to be the most consistent and significant prognostic indicator in the literature. [48][49][50][51][52][53][54][55][56][57][58] However, recurrence and metastasis among patients with stage I LMS are not uncommon. 55,57 In our study, tumour-related deaths or recurrences were observed in 45.5% (15/33) of stage I LMSs.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] In a review of 208 patients with LMS, Giuntoli et al reported that adjuvant pelvic RT did not improve the survival rate. 11 Omura et al reported that there was no significant difference in the recurrence rate in a randomized clinical trial of adjuvant doxyrubicin therapy in uterine sarcoma. 12 Dinh et al also reported that current chemotherapy drugs are minimally effective for uterine LMS.…”
Section: Discussionmentioning
confidence: 99%